A future interstellar probe on the dynamic heliosphere and its interaction with the very local interstellar medium: In-situ particle and fields measurements and remotely sensed ENAs - Dialynas, K.; Sterken, V. J.; Brandt, P. C.; Burlaga, L.; Berdichevsky, D. B.; Decker, R. B.; Della Torre, S.; DeMajistre, R.; Galli, A.; Gkioulidou, M.; Hill, M. E.; Krimigis, S. M.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
The recently published Interstellar Probe (ISP) study report describes a pragmatic mission concept with a launch window that starts in 2036 and is expected to reach several hundreds of astronomical units past the heliopause within a time frame of ≥50 years (https://interstellarprobe.jhuapl.edu/Interstellar-Probe-MCR.pdf). Following the ISP report, this paper, that will also be accessible from the Bulletin of the AAS (BAAS) in the framework of the Decadal Survey for Solar and Space Physics (Heliophysics) 2024-2033 (Dialynas et al. 2022a), aims to highlight the importance of studying the physics of the interactions pertaining to the expanding solar wind that meets the plasma, gas and dust flows of the very local interstellar medium, forming the complex and vast region of our astrosphere. We focus on three fundamental open science questions that reveal the dynamical nature of the heliosphere: (A) Where are the heliosphere boundaries and how thick is the heliosheath? (B) Is there a missing pressure component towards exploring the dynamics of the global heliosheath and its interaction with the very local interstellar medium? (C) Why does the shape and size of the global heliosphere appear different in different Energetic Neutral Atom energies? We argue that these questions can only be addressed by exploiting a combination of in-situ charged particle, plasma waves and fields measurements with remotely sensed Energetic Neutral Atoms that can be measured simultaneously from the instruments of a future Interstellar Probe mission, along its trajectory from interplanetary space through the heliosheath and out to the very local interstellar medium.